Homelessness and other social determinants of health among emergency department patients. Issue 2 (2nd July 2016) - Doran, Kelly M.; Kunzler, Nathan M.; Mijanovich, Tod; Lang, Samantha W.; Rubin, Ada; Testa, Paul A.; Shelley, Donna
Abstract: Emergency departments (EDs) are often called the 'safety net' of the U.S. health care system. Little is known, however, about the social determinants of health (SDOH) – including rates and types of homelessness – of ED patients. This study sought to quantify the presence of housing instability, homelessness, and other selected SDOH in ED patients. We conducted a cross-sectional survey of a random sample of 625 patients presenting to an urban ED. 13.8% of patients were currently living in a homeless shelter or on the streets. Further, 25.4% of patients reported concern about becoming homeless in the next 2 months and 9.1% had been evicted in the past year. 42.0% of patients reported difficulty meeting essential expenses and 35.9% were worried about running out of food. In conclusion, we found high rates of homelessness and other social needs in ED patients. Addressing patients' SDOH will become increasingly important under new healthcare payment models.